Assessing the Rwanda experiment: popular perceptions of gacaca in its final phase - Pozen, Joanna (International journal of transitional justice, 2014)
Gacaca trials raise the question of whether a transitional justice mechanism instituted at the community level can successfully reconcile and bring justice to postconflict states. In this article, we assess ordinary Rwandans’ attitudes towards gacaca to better understand this institution’s contribution. Our 2011 survey of 504 Rwandans from Ngoma Commune is the first empirical study since the end of regular gacaca trials. In it we find that respondents hold conflicting views of gacaca’s overall success. The majority of survey participants expressed support in response to more global questions, but dissatisfaction with gacaca in response to more specific questions, including regarding security and the credibility of confessions. Rather than dismiss positive global assessments, we suggest that divergent attitudes show popular support for the idea of gacaca and aspirations for its legacy, but dissatisfaction with its actual operation.